VD_FINDINFO Jug / 2015 / 281 vom 26. Mai 2015 - VD Tribunal cantonal (2015)
DROIT D'AUTEUR ET DROITS VOISINS, INTÉGRITÉ DE L'OEUVRE, DROIT MORAL, ACTION EN INTERDICTION, EXÉCUTIONPROCÉDURE | 11 LDA, 62 LDA, 236 CPC (CH), 343 al. 1 let. a CPC (CH)